2021
DOI: 10.1108/apjba-09-2021-0430
|View full text |Cite
|
Sign up to set email alerts
|

A bibliometric analysis of peer-reviewed literature on smartphone addiction and future research agenda

Abstract: PurposeWith the rise in adverse impact of excessive technology use, such as smartphone; the issue of smartphone addiction has gained the attention of researchers in recent years. Therefore, this study undertakes to review the literature on smartphone addiction research by identifying the current state of research in this domain and the future avenues that need to be addressed.Design/methodology/approachA comprehensive bibliometric analysis was conducted on 652 articles extracted from SCOPUS database. Publicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 68 publications
(91 reference statements)
0
4
0
Order By: Relevance
“…Previous studies have revealed the detrimental impacts of social media addiction on users' health. A systematic review by Khan and Khan ( 20 ) has pointed out that social media addiction has a negative impact on users' mental health. For example, social media addiction can lead to stress levels rise, loneliness, and sadness ( 54 ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have revealed the detrimental impacts of social media addiction on users' health. A systematic review by Khan and Khan ( 20 ) has pointed out that social media addiction has a negative impact on users' mental health. For example, social media addiction can lead to stress levels rise, loneliness, and sadness ( 54 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Diagnostic research may be useful in order to understand social media behavioral addiction and gain deeper insights into the factors responsible for psychological stress and psychiatric disorders. In addition to cross-sectional studies, researchers should also conduct longitudinal studies and experiments to assess changes in users' behavior over time ( 20 ).…”
Section: Research Directions For Future Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the internet is an essential part of daily life, in recent years there has been a plethora of research on its psychosocial impact (Khan & Khan, 2022). Despite being largely beneficial for information access, time management, and communication (Castellacci & Tveito, 2018), digital technologies and internet usage may become problematic, or even addictive, for about one-quarter of individuals (Meng et al, 2022;Pan et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…That possibly is the prime reason for individuals/customers to be ‘addicted’ to smartphones. Extant research on the phenomenon of ‘smartphone addiction’ has been limited to a few countries, mainly concentrated in the fields of medicine and psychology (Khan & Khan, 2022). Prior studies do not seem to have sufficiently addressed the impact of technology and marketing‐related factors in promoting smartphone addiction, vis‐à‐vis its more prominent effects on mobile purchase behaviour, more so within the Indian context.…”
Section: Introductionmentioning
confidence: 99%